Syrian Adolescent Refugees: How Do They Cope During Their Stay in Refugee Camps? - Braun-Lewensohn, Orna; Al-Sayed, Khaled (Frontiers in Psychology, 2018)
To date, more than 11 million Syrians have been forced from their homes due to the civil war in that country. However, little research has been done on adolescent Syrian refugees. This study aimed to fill that gap in the research literature by examining how adolescent Syrian refugees cope with the harsh situation of having fled from their homes. We explored how personal-capital factors, sense of coherence (SOC), wishes and expectations, as well as socio-demographic and situational factors, contribute to a variety of mental health and psychological problems, namely, internalizing and externalizing problems and post-traumatic stress symptoms. Data were gathered from 110 adolescents aged 13–18 of whom 50.9% were boys. Participants filled out self-report questionnaires that asked about demographics, exposure to war, appraisal of danger, receiving aid, SOC, wishes and expectations. They also completed the Achenbach Youth Form. The results show that girls appraised their situation as more dangerous and reported more internalizing, externalizing and post-traumatic stress symptoms. In contrast, boys reported more exposure to war experiences and stronger SOC. Younger adolescents reported stronger SOC while older adolescents reported more psychological problems. The adolescents who had more recently arrived in the refugee camp were in better condition, reporting stronger SOC, higher expectations and fewer psychological problems. The amount of time spent in the refugee camp, gender, exposure to war situations and appraisal of danger all contributed to the explained variance in the different psychological problems. However, once the personal resource SOC was entered into the model, it mediated the relationships between all of the socio-demographic and situational variables, on the one hand, and the examined psychological problems, on the other. The results are discussed based on the personal-capital model of salutogenesis and its relations with traumatic stress.